Effects of adding single joint exercises to a resistance training programme in trained women - Barbalho, M.; Silveira Coswig, V.; Raiol, R.; Steele, J.; Fisher, J.; Paoli, A.; Gentil, P. (Sports, 2018)
Background: The present study`s aim was to compare the changes in muscle performance and anthropometric measures in trained women performing RT programs composed only of MJ exercises or programmes that involve the addition of SJ exercises. Methods: Seventeen trained women were randomised to MJ or MJ+SJ. Both groups performed the same MJ exercises following a nonlinear periodisation model for 8 weeks. The only difference was that the MJ+SJ group also performed SJ exercises. The participants were tested for 10 repetition maximum (10 RM), flexed arm circumference, and both biceps and triceps skinfold. Results: Both groups significantly increased 10 RM load for the bench press (12.6% MJ and 9.2% MJ+SJ), triceps (15.6% MJ and 17.9% MJ+SJ), pull down (9.8% MJ and 8.3% MJ+SJ), biceps (14.0% MJ and 13.0% MJ+SJ), leg press (15.2% MJ and 12.8% MJ+SJ) and knee extension (10.2% MJ and 9.1% MJ+SJ). The decreases in triceps (-5.1% MJ and -5.3% MJ+SJ) and biceps (-6.5% MJ and -5.7% MJ+SJ) skinfolds were also significant as were the increases in arm circumference (1.47% MJ and 1.58% MJ+SJ). In all tests there was nothing significantly different between groups. Conclusions: The use of SJ exercises as a complement to a RT programme containing MJ exercises brings no additional benefit to trained women.